Moving Northwards: Life-History Traits of the Invasive Green Crab (Carcinus maenas) Expanding into the Southwestern Atlantic - Micaela Müller Baigorria; Maite Narvarte; Leandro A. Hünicken (Biology)
The invasive European green crab (Carcinus maenas) poses a significant ecological threat due to its rapid global spread and disruptive impact on coastal ecosystems. In the southwestern Atlantic, the northernmost population was recently recorded in the San Matías Gulf, offering a unique opportunity to study its demographic and life-history traits at the leading edge of its range. We assessed the sex ratio, population density, size distribution, and size at which 50% of females were ovigerous (SM50) in the intertidal zone. Our findings revealed a male-biased sex ratio (1.50 males per female) and low population density (0.42 crabs m−2), suggesting early-stage establishment. A size-structure analysis showed a well-structured population with clear cohort separation in both sexes and evidence of two recruitment events. The carapace width at which 50% of females were ovigerous was estimated at 61.48 mm. Although egg-bearing females exhibited a well-marked seasonality, with the highest prevalence from May to July, their presence nearly year-round suggests an extended reproductive period and adaptability to local conditions, which may be advantageous in recently established populations, facilitating invasion success. These traits, combined with the species’ ongoing range expansion, highlight the invasive potential of C. maenas and its possible ecological impacts on the San Matías Gulf.